Visualizing maritime connectivity at national level: The case of LSBCI links of West European countries. Issue 4 (December 2021) - Guerrero, David; Niérat, Patrick; Thill, Jean-Claude; Cohen, Emmanuel
Highlights: We propose a LSBCI visualization based on Multi-Dimensional Scaling (MDS). The visualization clearly shows a core and a periphery in the country network. There is a pack of European countries positioned at the core of the network. Some European countries are positioned far away. Some peripheral countries are closer to Asia than to Europe. Abstract: The Liner Shipping Bilateral Connectivity Index (LSBCI), proposed by UNCTAD 1, aims to measure the quality of maritime transport connections between countries. Although its main geographical scope is the developing world, it is increasingly used by scholars and practitioners within the context of developed countries. But its relevance and applicability remain to be assessed. As a first step in this direction, this paper proposes a visualization of the LSBCI based on Multi-Dimensional Scaling (MDS). The paper is focused on the connections of 10 West European countries among them and with the rest of the world. The MDS visualization clearly shows a core and a periphery in the containerized shipping network. While some proximities between countries can be explained by geographical proximity, others exclusively result from other factors such market structure and network considerations.